NirA is an alternative nitrite reductase from Pseudomonas aeruginosa with potential as an anti-virulence target - Fenn, Samuel Jacob (2022)
Pseudomonas aeruginosa is capable of causing a wide-range of diseases due to production of an extensive arsenal of virulence factors. This opportunistic pathogen is capable of causing both acute and chronic infection, with treatment complicated due to its intrinsic resistance and tolerance of antibiotics. With the antibacterial pipeline drying up, anti-virulence therapy has become an attractive alternative strategy to the traditional use of antibiotics to treat P. aeruginosa infections. The work presented in this thesis builds upon the successful ‘integrated whole-genome screening for Pseudomonas aeruginosa virulence genes using multiple disease models’, performed in our lab as part of the NABATIVI project to combat anti-virulence target identification.